Deconvolution of Light‐Induced Ion Migration Phenomena by Statistical Analysis of Cathodoluminescence in Lead Halide‐Based Perovskites. Issue 13 (3rd March 2022) - Shirzadi, Erfan; Tappy, Nicolas; Ansari, Fatemeh; Nazeeruddin, Mohammad Khaja; Hagfeldt, Anders; Dyson, Paul J.
Abstract: Studying the compositional instability of mixed ion perovskites under light illumination is important to understand the mechanisms underlying their efficiency and stability. However, current techniques are limited in resolution and are unable to deconvolute minor ion migration phenomena. Here, a method that enables ion migration to be studied allowing different segregation mechanisms to be elucidated is described. Statistical analysis is applied to cathodoluminescence data to generate compositional distribution histograms. Using these histograms, two different ion migration phenomena, horizontal ion migration (HIM) and vertical ion migration (VIM), are identified in different perovskite films. It is found that most passivating agents inhibit HIM, but not VIM. However, VIM can be reduced by deposition of imidazolium iodide on the perovskite surface. This method can be used to study perovskite‐based devices efficiency and stability by providing molecular level mechanistic understanding of passivation approaches leading to performance improvement of perovskite solar cells via rational design. Abstract : Light causes ions to migrate two different directions in organic/inorganic lead halide: horizontal and vertical. A method combining cathodoluminescence and statistics is developed that quantifies the different types of ion migrations for both halides and cations in different types of perovskites. A possible mechanism for different modes of ion migration is discussed.